The Urgency of Parental Piety in Preserving the Blessings of Their Offspring (Comparative Study of Tafsir Al-Munir and Ibn Kathir: Surah Al-Kahfi, Verse 82) - Narotama, Syahrul Abdi; Rhain, Ainur; Dahliana , Yeti; Nurrohim, Ahmad; Azizah, Alfiyatul (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
In the context of family life, parents are considered a very important factor in creating and maintaining blessings for their children. The piety or righteousness of parents becomes the cause of Allah's mercy and protection not only for themselves but also for their descendants. Therefore, this article discusses the significance of parental righteousness, which has a profound impact on Allah's protection of their offspring, through the perspective of exegeses on Surah Al-Kahfi, verse 82. This article adopts a thematic tafsir approach by comparing the explanations of classical and contemporary scholars, namely Ibn Kathir and Wahbah Az-Zuhaili, on the key study of Surah Al-Kahfi, verse 82. The first part of this discussion introduces brief biographies of the two scholars, their tafsir writing systems, and the approaches to interpretation they employed. It then presents their respective interpretations before comparing the two. The findings of this research show that parental righteousness is highly relevant in safeguarding the blessings for their descendants. Both tafsirs agree that parental piety plays a key role in determining blessings, both in material aspects (such as protection of wealth) and spiritual aspects (such as divine guidance and the safety of children in this life and the hereafter).